Using Planar Laser Induced Fluorescence to explain the mechanism of heterogeneous water droplet boiling and explosive breakup; Experimental Thermal and Fluid Science; Vol. 91 - Piskunov M. V. Maksim Vladimirovich (2018, 2018)
Title screen